An Evaluation of the Impact of a Faith-Based Volunteer Program. (September 2014) - Yamada, Mieko; Gutierrez, Daniel
This paper presents a study undertaken to evaluate the impact of a faith-based volunteer program in Fort Wayne, Indiana, and determine how effectively the program serves to connect volunteers, agencies, and the local community. Organizational factors, such as volunteer training, task preparation, and support within the program, affect levels of volunteers' performance and satisfaction. Based on the volunteers' and agencies' input regarding the faith-based volunteer program, we examine how faith-based volunteers perceived their own experiences related to their host program and to what extent they felt satisfied with their assigned work. We discuss survey and interview findings and suggest the need for further research among volunteer organizations.